8(-3b+6)=96

Simple and best practice solution for 8(-3b+6)=96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(-3b+6)=96 equation:


Simplifying
8(-3b + 6) = 96

Reorder the terms:
8(6 + -3b) = 96
(6 * 8 + -3b * 8) = 96
(48 + -24b) = 96

Solving
48 + -24b = 96

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-48' to each side of the equation.
48 + -48 + -24b = 96 + -48

Combine like terms: 48 + -48 = 0
0 + -24b = 96 + -48
-24b = 96 + -48

Combine like terms: 96 + -48 = 48
-24b = 48

Divide each side by '-24'.
b = -2

Simplifying
b = -2

See similar equations:

| 1.3n-.03=9 | | 4xy^2/y | | 20×1/4 | | x^2-40=41 | | 3(2l+10)=48 | | y+x=10-4 | | 3x+22=x+4 | | 0.6(x-1)+0.2x=6.6 | | y=-2.1x+3.4 | | -x-19=2x+8 | | 49=-7z | | y=2x^2-36x+c | | -2(x+2)+3=3(x+3)+4 | | (x-2)(x-2)+(y-6)(y-6)=25 | | 2+f=-3 | | x-6+x=78 | | -y/4=-16 | | 2x=960 | | x^3+4=13 | | -6(2t+8)=-108 | | 43+x=-37 | | x^4+5x^3-x^2-12x-6=0 | | 7x+21=3x+1 | | -6(27+8)=-108 | | b-38=-28 | | -3x^2+9x=2 | | 3(1.5+5y)=30 | | -6(27+8)=-180 | | 3(1+5y)=30 | | -11z=99 | | 2log(x)-Log(4)=Log(x+15) | | 3(5.0+5y)=30 |

Equations solver categories